2012
DOI: 10.1016/j.enpol.2012.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Green jobs? Economic impacts of renewable energy in Germany

Abstract: Abstract:The labor market implications of large investment into renewable energy (RE) are analyzed in this text. Although a growing RE industry can be observed in Germany the overall effect of large increases of expensive electricity and heat generating technologies on the German economy require a careful model based analysis. The paper shows the overall effects under different assumptions for fossil fuel prices, domestic installations and international trade. Most of these scenarios exhibit positive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(75 citation statements)
references
References 18 publications
3
63
0
1
Order By: Relevance
“…Additionally, to the extent that increased wind impacts the cost of energy, or has other macroeconomic effects, this too may affect employment in the broader economy. Studies that have evaluated the economy-wide net effects of renewable energy have shown differing results (e.g., Böhringer et al 2013;Böhringer et al 2012;Bowen et al 2013;Breitschopf et al 2011;Chien and Hu 2008;Frondel et al 2010;Hillebrand et al 2006;Lehr et al 2012;Lehr et al 2008;Marques and Fuinhas 2012;Menegaki 2011;Rivers 2013;Yi 2013). In general, however, there is little reason to believe that net impacts are likely to be sizable in either the positive or negative direction (e.g., Rivers 2013).…”
Section: Workforce and Economic Developmentmentioning
confidence: 98%
“…Additionally, to the extent that increased wind impacts the cost of energy, or has other macroeconomic effects, this too may affect employment in the broader economy. Studies that have evaluated the economy-wide net effects of renewable energy have shown differing results (e.g., Böhringer et al 2013;Böhringer et al 2012;Bowen et al 2013;Breitschopf et al 2011;Chien and Hu 2008;Frondel et al 2010;Hillebrand et al 2006;Lehr et al 2012;Lehr et al 2008;Marques and Fuinhas 2012;Menegaki 2011;Rivers 2013;Yi 2013). In general, however, there is little reason to believe that net impacts are likely to be sizable in either the positive or negative direction (e.g., Rivers 2013).…”
Section: Workforce and Economic Developmentmentioning
confidence: 98%
“…New, partly international, production chains develop. To adequately account for these changes, input-output structures for the RPGT have been implemented in the model, based on a comprehensive industry survey and earlier work [10]. This kind of enlarged macro model with an input-output core is able to take these changes towards renewable power generation into account.…”
Section: Economic Impacts Of Rpgt Deployment: International Dimensionmentioning
confidence: 99%
“…Assumptions on future development of exports of RPGT are the most important driver for future economic net impacts in national studies [10], [30]. They depend on new installations in foreign markets, which are driven by global learning and national support policies.…”
Section: Economic Impacts Of Rpgt Deployment: International Dimensionmentioning
confidence: 99%
See 2 more Smart Citations